Waktu Inkubasi pada Derajat Distilasi Kitosan Enzim dan Efektifitas Penghambatannya terhadap Penyakit Antraknosa - Yadi Suryadi; Tri Puji Priyatno; I Made Samudra; Dwi Ningsih Susilowati; Hermawati Nurzulaika; Syaefudin Syaefudin (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
The use of chitosan as a coating agent of harvested fruits is an alternative method in controlling anthracnose disease (Colletotrichum sp.). This study aimed to obtain an optimal enzymatic chitosan (EC) that hydrolyzed using chitinase from Burkholderia cepacia isolate E76. The optimal incubation condition to produce EC was 2 h with the yield of 3.52 ± 0.38 g. The degree of deacetylation (DD) chitosan and EC was 66.91% and 80.91%, respectively. Based on in vitro assays, EC 2% was the most effective in inhibiting the growth of Colletotrichum sp. (94.22%) than chitosan, while the highest inhibition for chitosan 3% was 55.26%. Moreover, the EC 2% showed the highest inhibition of spore germination (74.12%). The in vivo assay revealed that EC 2% showed the highest inhibition on the fungal growth (88.88%), compared to the other concentrations. On the other hand, the EC 2% and 3% gave similar results on inhibition of Colletotrichum sp.of chili (55.55%).